Pengembangan Perangkat Pembelajaran Langsung dengan Media Animasi Berbasis Flash pada Materi Kubus dan Balok - Ria Fibriana Sari; I Ketut Budayasa; Agung Lukito (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2020)
This research is triggered by low students learning outcomes in cube and cuboid material. It was occured because teacher was dominating learning activities. As a resuly, an alternatif learning activities based on flash based animation media. This research is a development of research. The purpose of this research is to produce the direct learning based on Macromedia Flash device which can improve student learning outcomes in class VIII on the topic cube and cuboid. Development of a learning device performed using 4-D models (model Thiagarajan et al). Learning device produced in the form of: (1) Lesson Plan (RPP), (2) Introductional Media Based on Macromedia Flash, (3)Student Worksheet (LKS), and (4) Learning Outcomes (THB).Based on the results of the test device, obtained by the direct learning based on Macromedia Flash have been valid according to the validator and qualified: (1) the ability to manage the learning criteria of good teachers, (2) the activity of students active in the learning process, (3) Classical learning completeness reached, (4) students response positive a learning component, (5) the learning outcomes test meet the criteria for a valid, reliable, and sensitive. Thus, it can be concluded that problem based learning was effective.